The potential clinical utility of measuring severe acute respiratory syndrome coronavirus 2-specific T-cell responses. (December 2021) - Goletti, Delia; Petrone, Linda; Manissero, Davide; Bertoletti, Antonio; Rao, Sonia; Ndunda, Nduku; Sette, Alessandro; Nikolayevskyy, Vladyslav
Abstract: Background: Both humoral and cell-mediated responses are associated with immunity to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Although our understanding of the potential role of T-cell responses in the context of coronavirus disease 2019 (COVID-19) is rapidly increasing, more information is still needed. Objectives: To provide an overview of the role of T-cell immunity in COVID-19, in the context of natural infection and post-vaccination, and discuss the potential utility of measuring SARS-CoV-2-specific T-cell responses, drawing on experience of the use of interferon-γ release assays (IGRAs) in tuberculosis (TB). Sources: PubMed articles up to 16 April 2021. Content: T-cell responses can be detected very early in the course of COVID-19, earlier than the detection of antibody responses, and are correlated with COVID-19 outcome. Lower CD4 + and CD8 + T-cell counts are markers of more severe disease, longer duration of viral RNA positivity and increased mortality. In line with natural infection, SARS-CoV-2 vaccination stimulates robust T-cell responses, which probably play an important role in protection; data on long-term T-cell responses are currently limited. The utility of measuring T-cell responses is already well established in both aiding the diagnosis of TB infection using IGRAs, and evaluation of T-cell responses to TB vaccine candidates. A variety of assays have already been developed to measure SARS-CoV-2-specific T-cell responses, including IGRAs, intracellular cytokine staining and activation-induced markers. IGRAs based on SARS-CoV-2 antigens can distinguish between convalescent and uninfected healthy blood donors. Implications: Simple assays for measuring the quantity and function of T-cell responses may have utility in the prognostication of COVID-19, and for monitoring immune responses to SARS-CoV-2 vaccination and population-based immunity to SARS-CoV-2 variants of interest.